PENGARUH STRATEGI STRENGTHENING, ORIENTATION, INVESTIGATION, EVALUATION (SOIE) TERHADAP LITERASI KIMIA PESERTA DIDIK - Fadli, Mhd Ridwan; Fitriani, Henni; Mellyzar, Mellyzar; Alvina, Sirry; Muttakin, Muttakin; Fakhrah, Fakhrah (Jurnal Dedikasi Pendidikan, 2024)
This research aims to determine the influence of the Strengthening, Orientation, Investigation, Evaluation (SOIE) strategy on students' chemical literacy at SMA Negeri 1 Lhokseumawe. This research was carried out in the odd semester of the 2023/2024 academic year in classes XI-1 and XI-4. The type of research used is quasi-experiment (quasi-experiment) with a quantitative approach. The sampling technique in this research is purposive sampling. The sample in this study was class X1-I as an experimental class with a total of 36 students and class XI-4 as a control class with a total of 33 students. The research sample has been tested for normality and homogeneity requirements. The data collection technique uses essay questions. The test was carried out at the end (posttest) in the experimental class and control class. Hypothesis testing using the Mann-Whitney test, obtained a sig value. (2-tailed) 0.001 < 0.05 on posttest results. Based on the test results, it can be concluded that there is an influence of the SOIE strategy on students' chemical literacy at SMA Negeri 1 Lhokseumawe and the SOIE strategy can contribute positively to students' chemical literacy on reaction rate material according to the sig value. (2-tailed) 0.000 < 0.05 and strengthens understanding of concepts and encourages active involvement of students in the chemistry learning process.